Interaction of adhered metallic dust with transient plasma heat loads. (17th May 2016) - Ratynskaia, S.; Tolias, P.; Bykov, I.; Rudakov, D.; De Angeli, M.; Vignitchouk, L.; Ripamonti, D.; Riva, G.; Bardin, S.; van der Meiden, H.; Vernimmen, J.; Bystrov, K.; et al.
Abstract: The first study of the interaction of metallic dust (tungsten, aluminum) adhered on tungsten substrates with transient plasma heat loads is presented. Experiments were carried out in the Pilot-PSI linear device with transient heat fluxes up to 550 MW m −2 and in the DIII-D divertor tokamak. The central role of the dust-substrate contact area in heat conduction is highlighted and confirmed by heat transfer simulations. The experiments provide evidence of the occurrence of wetting-induced coagulation, a novel growth mechanism where cluster melting accompanied by droplet wetting leads to the formation of larger grains. The physical processes behind this mechanism are elucidated. The remobilization activity of the newly formed dust and the survivability of tungsten dust on hot surfaces are documented and discussed in the light of implications for ITER.